Future Uses of Three/Four Dimensional Power Doppler Signal in Fetal Medicine - Bello-Munoz, Juan Carlos; Ayala, Mauricio; Carreras, Elena; Oliveros, Paula; Campo, Nazareth; Casasbuenas, Alexandra; Arévalo, Silvia; Cabero, Lluis (IntechOpen, 2012)
None